Scleritis in patients with granulomatosis with polyangiitis (Wegener). Issue 8 (13th November 2015) - Cocho, Lidia; Gonzalez-Gonzalez, Luis Alonso; Molina-Prat, Nicolas; Doctor, Priyanka; Sainz-de-la-Maza, Maite; Foster, C Stephen
Abstract : Aims: To describe and compare clinical features, complications and outcomes in patients with granulomatosis with polyangiitis (GPA)-associated scleritis with those seen in idiopathic and other autoimmune-associated scleritis, and to further describe the features that may serve as an indicator of life-threatening systemic disease. Methods: We retrospectively reviewed electronic health records of all patients with scleritis seen at two tertiary care centres. Of 500 patients, 14 had GPA-associated scleritis and were included in this analysis. Measures included were age, gender, laterality, visual acuity and underlying systemic or ocular diseases. Clinical features (location, pain, inflammation) and ocular complications of these patients (decrease of vision, concomitant anterior uveitis and ocular hypertension) were studied and correlated. Results: Fourteen of 500 patients with scleritis were GPA associated. Most of the patients with GPA-associated scleritis presented with sudden onset, bilateral, diffuse anterior scleral inflammation, with moderate-or-severe pain. Vision loss was not significantly different, and pain was more severe in these patients than in those with idiopathic scleritis. When compared with patients with other underlying autoimmune diseases, there were no significant differences found in epidemiological or clinical signs. Necrotising scleritis and corneal involvement were more commonly observed in GPA than in idiopathic scleritis and other autoimmune diseases and are often the presenting feature of the disease. Conclusions: The presence of necrotising changes or corneal involvement in the setting of scleral inflammation is highly suggestive of an underlying systemic vasculitis, of which GPA is the most common. These features should alert the doctor/optometrist and prompt a thorough diagnostic approach and an aggressive treatment given that it could reveal a life-threatening disease.